Fenômenos de desigualdade: uma investigação sobre a segregação socioespacial na Vila União, Zona Norte de Sorocaba - Lomardo, Juan (2021)
The present research consists of an effort to debate the concept of socio-spatial segregation, with the observations carried out in the Vila União occupation, located in the North Zone of the municipality of Sorocaba, in the countryside of São Paulo. Based on what was verified in the place, the notion of segregation of segregation is used, analyzed based on the concepts of reproduction of urban space and unequal geographic development. Understanding the urbanization process in capitalist society as critical urbanization, the aim of the research was also the counter-hegemonic possibilities of the place, visualized in the resistance actions of the population of the Vila União occupation.